Conditional Expression of Human PPARδ and a Dominant Negative Variant of hPPARδ In Vivo - Larry G. Higgins; Wojciech G. Garbacz; Mattias C. U. Gustafsson; Sitheswaran Nainamalai; Peter R. Ashby; C. Roland Wolf; Colin N. A. Palmer (PPAR Research)
The nuclear receptor, NR1C2 or peroxisome proliferator-activated receptor (PPAR)-δ, is ubiquitously expressed and important for placental development, fatty acid metabolism, wound healing, inflammation, and tumour development. PPARδ has been hypothesized to function as both a ligand activated transcription factor and a repressor of transcription in the absence of agonist. In this paper, treatment of mice conditionally expressing human PPARδ with GW501516 resulted in a marked loss in body weight that was not evident in nontransgenic animals or animals expressing a dominant negative derivative of PPARδ. Expression of either functional or dominant negative hPPARδ blocked bezafibrate-induced PPARα-dependent hepatomegaly and blocked the effect of bezafibrate on the transcription of PPARα target genes. These data demonstrate, for the first time, that PPARδ could inhibit the activation of PPARα in vivo and provide novel models for the investigation of the role of PPARδ in pathophysiology.